DEVELOPMENT AND IN-VITRO CHARACTERISATION OF CHITOSAN LOADED PACLITAXEL NANOPARTICLE - Sarkar, Tumpa; Ahmed, Abdul Baquee (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To meet the above aim the following objectives are undertaken: (1) Preparation of paclitaxel (PTX) loaded nanoparticles by different techniques, (2) In-vitro evaluations of the drug loaded nanoparticles and selection of optimized batch. Methods: PTX loaded chitosan nanoparticles were prepared by Ionic-crosslinking technique. In this technique, chitosan was dissolved in 0.25%v/v acetic acid solution. To this above solution 0.84%v/v, glutaraldehyde solution was added dropwise under high-speed homogenizer at 17000 rpm for 1 hr. Result: Particle size of prepared nanoparticle formulations was found to be 345.175±5.66-815.125±8.355 nm with low PDI between 0.456. The maximum entrapment of drug was found to be 88.57±2.533% with formulation F5. In-vitro release studies of the F5 formulation showed 57.8±1.735% release of drug after 24 hrs. Conclusion: The prepared nanoparticles were evaluated for its particle size, zeta potential, drug entrapment efficiency, in-vitro drug release study, and surface morphology studies by scanning electron microscopy. The results of Fourier transform infrared studies of 1:1 physical mixture of drug and excipients confirmed the absence of incompatibility. Thus, the study concludes that PTX loaded nanoparticles were developed successfully by ionic crosslinking method, which is expected to enhance the oral bioavailability of PTX. Keywords: Paclitaxel, Nanoparticles, Chitosan, Ionic-crosslinking, In-vitro release.